Origin and diversity of the words for ancient Eurasian grain legumes in Slavic languages - Mikic, Aleksandar (Onomázein, 2013)
This short research note aims at demonstrating the importance of the role that grain legumes, such as pea (Pisum sativum L.), lentil (Lens culinaris Medik.) or field bean (Vicia faba L.), have been playing in the everyday lives of both modern Slavic nations and their ancestors. This role has been witnessed by rather rich lexicological evidence and supported by attested etymological connections. This note also links Slavic roots to the other members of Indo-European language families and presents their common ProtoIndo-European origins.